1999
DOI: 10.1002/(sici)1097-4547(19990115)55:2<198::aid-jnr7>3.0.co;2-m
|View full text |Cite
|
Sign up to set email alerts
|

Expression of three forms of nitric oxide synthase in peripheral nerve regeneration

Abstract: Nitric oxide (NO) is a short-lived molecule with messenger and cytotoxic functions in nervous, cardiovascular, and immune systems. Nitric oxide synthase (NOS), the enzyme responsible for NO synthesis, exists in three different forms: the neuronal (nNOS), present in discrete neuronal populations; the endothelial (eNOS), present in vascular endotheliun, and the inducible isoform (iNOS), expressed in various cell types when activated, including macrophages and glial cells. In this study, we have investigated the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
28
1

Year Published

2001
2001
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(33 citation statements)
references
References 69 publications
2
28
1
Order By: Relevance
“…Previous studies have shown that the three NOS isoforms are overexpressed in different cell types 2 days after lesion, reaching their greatest expression during the second week [36]. However, we did not detect the higher expression of nNOS protein compared to normal control at 2 days after SNC.…”
Section: Discussioncontrasting
confidence: 95%
See 1 more Smart Citation
“…Previous studies have shown that the three NOS isoforms are overexpressed in different cell types 2 days after lesion, reaching their greatest expression during the second week [36]. However, we did not detect the higher expression of nNOS protein compared to normal control at 2 days after SNC.…”
Section: Discussioncontrasting
confidence: 95%
“…Accumulating evidence indicated that the three NOS isoforms were induced after peripheral nerve lesion [6,36,55,56]. Deficiency of nNOS led after sciatic nerve transection to a substantial loss of dorsal root ganglia neurons and spinal cord neurons, whereas a lack of eNOS or iNOS was well tolerated without consequences for neuronal survival [4][5][6][7].…”
Section: Discussionmentioning
confidence: 99%
“…Scale bar=100 μm Kikuchi R et al 22 be inflammatory cells were observed in the stump and were iNOS-positive. An iNOS-positive reaction was previously shown to be induced around the ligated region in response to compressive stimulation by sciatic nerve ligation 12) , suggesting that, in the present study, transection induced inflammatory cytokines, causing an inflammatory reaction. In contrast, no eNOS was expressed in the stump, indicating that it was not involved in the nerve regeneration process.…”
Section: Discussionsupporting
confidence: 63%
“…For example, nNOS is the dominant NO supplier to promote neuronal survival and recovery of DRG after peripheral nerve damage (Keilhoff et al 2003). It is also possible that NO is involved in several mechanisms related either to nerve regeneration or to the retrograde degeneration because peripheral axotomy leads to a significant increase in the small-and medium-sized NADPH-d/NOS-positive neurons in axotomized sensory ganglia (Wang et al 1996, Gonzales-Hernandez & Rustioni 1999, and to its de novo induction in MTN neurons (Varathan et al 2001). It seems likely that NADPH-d activity is plastic and can be up-regulated by a peripheral nerve injury (Vizzard et al 1995).…”
Section: Discussionmentioning
confidence: 99%